Variability of lightning, convective rain and solar activity study over South/Southeast Asia during ENSO episode for the period of 1998-2010 - Singh, Devendraa; Dharmaraj, T.; Kumar, P. Ramesh; Singh, Rajesh; Kumar, Sanjay; Chinthalu, G. R.; Patil, M. N.; Singh, R. P. (My University, 2017)
Analysis of monthly mean data of lightning and convective rain for the region 8° N - 35° N, 60° E - 120° E and for the period 1998-2010 show that lightning and convective rain are not significantly influenced by solar parameters such as sunspot number, total solar irradiance (TSI) and solar radio flux whereas CAPE anomaly and temperature anomaly have significant impact on the total lightning flash rate and convective rain during ENSO periods. Further no significant relation between cosmic ray flux and total lightning flash rate during La Niña period is obtained. On the other hand, for the El Niño period and for the total period, we get statistically some significant negative correlation between cosmic ray flux and total lightning flash rate. However, it is not possible to make any comment on the general relation between cosmic ray flux and total lightning flash rate due to contaminating global effects, regional effects and cloud microphysics. In the monthly variation of the parameters, temperature anomaly can be used as a proxy for the total lightning flash rate for the region under consideration. Most of the variation in ozone during the ENSO period is due to lightning. In the region considered here, role of aerosols in producing lightning and rainfall is quite comparable during La Niña period. On the other hand, aerosols contribute more towards production of lightning than producing rain during El Niño due to changes in cloud microphysics and cloud electrification.
Keywords: El Nino; La Nina; Lightning flash rate; ENSO; Convective rain rate; Cosmic rays; Solar activity; CAPE; Aerosol optical depth